ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI DAN TINGKAT PENDAPATAN USAHATANI PADI SAWAH PESERTA UPSUS PAJALE DI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Kresnalia Astasari; Wan Abbas Zakaria; Irwan Effendi (Lampung University, 2021)
The objectives of the research were to analyze the participation of farmers in the Upsus Program, to analyze the factors that affect rice production, and to analyze the income level of lowland rice farming in Gadingrejo Sub District, Pringsewu District. The research was conducted in March-April 2019. The analysis of farmerparticipation in the Upsus Pajale program using scoring technique which were processed into interval data with Methode of Succesive Interval. Factors that affecting rice production were analyzed using the Cobb Doughlass production function, and analysis of farm income using a comparison between total revenues and total costs, called Revenue Cost Ratio (R/C). The results of this study were farmers' participation in the Upsus Pajale program was in the middle class, the factors that affect the rice production of lowland rice farming, namely land area, amount of phonska fertilizer, pesticide and farmer participation. Income from cash costs obtained by farmers amounted to Rp18,116,478.41 with R/C of 6,23/0,73 ha/planting season and income to total costs amounted to Rp16,184,879.44 with an R/C of 4,00/0,73 ha/planting season.Keywords: factors, income, production, rice paddy